Design and Installation of Lightning Arrester System at Karitas Yogyakarta Junior High School - Widagdo, Reza Sarwo; Puji Slamet; Aris Heri Andriawan; Izzah Aula Wardah; Balok Hariadi; Iswahyudi, Yolan Bagus Putra (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2025)
The Karitas Yogyakarta junior high school building is located in Yogyakarta, standing on an area of 4,750 m² with two buildings of two floors each. This building is located near swamps and settlements between people's houses, and is surrounded by plantations and rice fields at the back. This building is not equipped with a lightning distribution system, even though tall buildings need this system to protect against the danger of lightning strikes. This research designs a lightning distribution system according to applicable standards, and the results show that the density of lightning strikes per year is 20.28 km²/year with the largest equivalent coverage area of 8,297.045466 m². The highest probability of a lightning strike to a building is 0.086 with protection level I for all buildings. To protect the entire building, 9 lightning rods are needed and the grounding system requires 3 electrode rods.